2018
DOI: 10.1039/c8ob00128f
|View full text |Cite
|
Sign up to set email alerts
|

Access to 2-substituted-2H-indazolesviaa copper-catalyzed regioselective cross-coupling reaction

Abstract: A CuCl catalyzed C-N cross-coupling reaction using commercially available 1H-indazoles with diaryliodonium salts is described. The methodology features ample structural versatility, affording 2-substituted-2H-indazole in good yields and complete N(2)-regiocontrol. Furthermore, the utility of the reaction was demonstrated in the synthesis of a known estrogen receptor β agonist. Mechanistic studies using density functional theory calculations suggested that the complete regioselectivity can be attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…2-substituted-2H-indazoles have been recognized as biologically privileged structures, exhibiting a wide range of biological properties such as anticancer activities. Reflecting this, their challenging synthesis under mild conditions was reported by Pan in 2018 [120]. Compared to the previously described C-N cross-coupling reaction starting from 1H indazoles, the use of hypervalent iodine reagent under the catalysis of copper led to N2 arylation in high selectivity.…”
Section: Metal-catalyzed N-h Arylation Of Heteroarenesmentioning
confidence: 98%
“…2-substituted-2H-indazoles have been recognized as biologically privileged structures, exhibiting a wide range of biological properties such as anticancer activities. Reflecting this, their challenging synthesis under mild conditions was reported by Pan in 2018 [120]. Compared to the previously described C-N cross-coupling reaction starting from 1H indazoles, the use of hypervalent iodine reagent under the catalysis of copper led to N2 arylation in high selectivity.…”
Section: Metal-catalyzed N-h Arylation Of Heteroarenesmentioning
confidence: 98%
“…In this method, 1H-indazoles (30 a) reacted with hypervalent iodine reagents such as p-tolyl (mesityl)iodonium triflate in presence of CuCl catalyst in dichloromethane solvent at 120°C for 12 h to afford 2-aryl-2H-indazoles (30 b) with moderate to very high yields (Scheme 30). [90] Electron-withdrawing as well as electron-donating substituents at C-4 to C-6 positions of 1H-indazoles were showing compatibility with this reaction and produced good to excellent yields. The group also demonstrated that both electron-withdrawing and electron-donating substituents at meta-and para-positions of the phenyl ring of diaryliodonium salt smoothly produced 2-arylated-2H-indazoles.…”
Section: Arylationmentioning
confidence: 88%
“…Due to great practical importance of N-arylated indazoles, over the past two decades methods for their design have been studied in detail and developed using both base and transition metal catalysis [14][15][16][17][18][19]. N-Arylation reactions of 1H-indazoles can proceed at both nitrogen atoms [14][15][16]. However, as a rule, the reaction proceeds regioselectively at the N 1 atom of the indazole ring [17][18][19].…”
Section: Doi: 101134/s1070363221060049mentioning
confidence: 99%